Game addiction : the experience and the effects - Clark, Neils; Scott, P. Shavaun (Jefferson, N.C. : McFarland & Co., 2009)
"This book studies videogame addiction from a cross-disciplinary approach, bridging the divide between liberal arts academics and clinical researchers. The topic of addiction is examined neutrally, using accepted research in neuroscience, media studies, and developmental psychology, among others, to reveal how today's gamers interact with and become consumed by the virtual worlds of their videogames"--Provided by publisher.
The digital living room -- Media experience and real illusion -- Why they play -- Anatomy of a game addiction -- Games are not babysitters -- The road ahead -- Appendix A. Helpful activities during the process of change -- Appendix B. Learning the lingo -- Appendix C. Commonly used Internet and gamer slang -- Appendix D. Seeking help in an unfamiliar world.
Includes bibliographical references (p. 187-199) and index.
Keywords: Video game addiction; Video games -- Psychological aspects; Video games and children; Video games and teenagers; Video games -- adverse effects; Video games -- psychology; Adolescent; Behavior, Addictive -- psychology; Child